2016
DOI: 10.1016/j.jconrel.2016.06.020
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticle-mediated miR200-b delivery for the treatment of diabetic retinopathy

Abstract: We recently reported that the Ins2Akita mouse is a good model for late-onset diabetic retinopathy. Here, we investigated the effect of miR200-b, a potential anti-angiogenic factor, on VEGF receptor 2 (VEGFR-2) expression and to determine the underlying angiogenic response in mouse endothelial cells, and in retinas from aged Ins2Akita mice. MiR200-b and its native flanking sequences were amplified and cloned into a pCAG-eGFP vector directed by the ubiquitous CAG promoter (namely pCAG-miR200-b-IRES-eGFP). The pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
37
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 51 publications
3
37
0
Order By: Relevance
“…The authors demonstrated experimentally that miR‐200b might alleviate DR development by down‐regulating its target gene VEGFA . Similar findings were obtained in Akita mice (a genetic model of diabetes) at 3 months after intravitreal injection of miR‐200b …”
Section: Discussionsupporting
confidence: 60%
See 3 more Smart Citations
“…The authors demonstrated experimentally that miR‐200b might alleviate DR development by down‐regulating its target gene VEGFA . Similar findings were obtained in Akita mice (a genetic model of diabetes) at 3 months after intravitreal injection of miR‐200b …”
Section: Discussionsupporting
confidence: 60%
“…Studies in vitro showed that miR‐200b is highly expressed in normal human retinal endothelial cells (hRECs), while it was down‐regulated under HG environment . Cell transfection with a miR‐200b mimic suppressed the migration of murine endothelial cells and the hRECs dysfunction by decreasing the levels of VEGF and transforming growth factor beta 1 (TGFB1), and by inhibiting vasohibin‐2, a protein that promotes the proliferation and migration of endothelial cells …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…MicroRNAs (miRNAs) are a class of naturally occurring small, non-coding RNA molecules. miRNA have been recognized as a key component in regulating cell biological development and may be involved in the pathogenesis of DR, therefore CK30-PEG nanoparticle-mediated miR200-b have been delivered for the treatment of diabetic retinopathy and lead to an effective anti-angiogenic therapy for DR (Mitra et al, 2016). Thus, Polymer NPs have a tolerable safety profile with a lack of immunogenicity in the retina, thus make CK30-PEG nanoparticles become a promising non-viral gene delivery vehicle for t ocular diseases.…”
Section: Polymer Nanoparticles Application In Ocular Diseasementioning
confidence: 99%